PEMBUATAN PERMAINAN LINK COLOUR BERBASIS ANDROID - Alexander Gregorius Pranoto; Budi Hartanto; Marcellinus Ferdinand Suciadi (CALYPTRA, 2018)
Casual Game Is a genre of the game which has same pattern and short level. For the example of the casual game is Catch Dot. Catch Dot is a game which has genre Casual Whom the player must match the color of the dot Which coming to circle in the center of the screen. Game will be over if the player can not match the color of the dot. At first, Catch Dot is very attractive, however, because of the lackof some features and variation, this game is rarely played right now. Then, an opportunities arise to make a similar game with Catch Dot which is named Link Colour. Link Colour has some features dan variation which is never exist in Catch Dot. Some features will be added in the Link Colour are online multiplayer, pause button, tutorial, levelling, power up. Power up which will be used are power up to increase the player’s health, slowing the rotation of the enemy wheel, reverse the direction of the enemy wheel. Theaddition ofthis feature are expected to make the Link Colour game can be more exciting thanthe CatchDot game and can be sought bymany people. Link Colour game uses Android Operating System. The development of Link Colour Game uses the Unity Game Engine and utilizing C# Programming Language. After implementation and some test run, obtained a result for Link Colour game. Link Colour game is exciting and easy to be played.